Financial literacy among petty traders. Evidence from the Kumasi metropolis. - NTIAMOAH, FRANCIS AGYARKO (KNUST, 2025)
A Thesis Submitted To Department Of Accounting And Finance In Partial Fulfillment Of The Requirements For The Degree Of Masters In Business Administration (Finance).